THE IMPORTANCE OF FOOTBALL AND ITS BASIC CHALLENGES IN LINGUISTIC POINT OF VIEW - Khasanov Zafar Bakhtiyorovich (Western European Studies, 2024)
Soccer, or football, is a widely known sport in many countries. In broadcasted matches, announcers (or commentators) have an important role of delivering the occurrences of the match to the audience. Since sport announcers‟ language form has its own uniqueness, sport announcers‟ language style is considered as a set of register called Sport Announcer’s Talk (SAT). This article is based on finding out the Individual Linguistic Features in the register of sport announcers. The study was done through transcribing the commentaries of certain matches and then categorizing the utterances into the proper Individual Linguistic Features.
Keywords: Football; commentary; commentators; register